2017
DOI: 10.1358/dof.2017.042.01.2564104
|View full text |Cite
|
Sign up to set email alerts
|

Targeting neuroinflammation in the treatment and prevention of Alzheimer's disease

Abstract: hyperphosphorylation and reduces memory loss. Thus, the emerging role of peripheral leukocytes in the pathogenesis of AD opens new avenues of investigation and may lead to the identification of new therapeutic approaches. This review summarizes our current understanding of the roles of vascular inflammation and circulating leukocytes in AD, focusing on recently discovered neuroinflammation mechanisms. We also discuss a role for adhesion molecules, chemokines and other inflammation mechanisms that may promote b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 279 publications
(437 reference statements)
0
6
0
1
Order By: Relevance
“…LFA-1 integrin blockade or neutrophil depletion at the inception AD had a significant ability to decrease memory deficits and other neuropathological hallmarks in AD-like mouse models. 125 This clearly demonstrates the role of neutrophils in the induction of cognitive dysfunction. Also, at the earlier stages of the disease, brief suspension of neutrophils had an effective long-term effect on older animals, which shows that neutrophils are indeed vital for the development of a chronic disorder.…”
Section: ■ Disease Modifying Strategiesmentioning
confidence: 81%
“…LFA-1 integrin blockade or neutrophil depletion at the inception AD had a significant ability to decrease memory deficits and other neuropathological hallmarks in AD-like mouse models. 125 This clearly demonstrates the role of neutrophils in the induction of cognitive dysfunction. Also, at the earlier stages of the disease, brief suspension of neutrophils had an effective long-term effect on older animals, which shows that neutrophils are indeed vital for the development of a chronic disorder.…”
Section: ■ Disease Modifying Strategiesmentioning
confidence: 81%
“…Furthermore, upregulation of the pro-inflammatory chemokine CCL3 was detected in both CSF and serum of App NL–G–F compared to WT mice. CCL3 is said to exert neuronal damage and deleterious effects on synaptic plasticity and learning performance by contributing to CNS inflammation by promoting migration of T-lymphocytes into the brain ( Marciniak et al, 2015 ; Zenaro and Constantin, 2017 ; Martin and Delarasse, 2018 ). The induction of (neuro-) inflammatory processes is one hallmark of the AD-like pathology in App NL–G–F KI mice, as summarized by the developers of the model ( Saito and Saido, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low-grade inflammation is thought to play a key role in the development of AD neuropathology. Previous studies of inflammation in AD have focused mainly on the activation of microglia 3 . However, several recent studies have shown that a dysfunctional blood–brain barrier associated with vascular inflammation and leukocyte migration into the brain contribute to the pathogenesis of AD 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of inflammation in AD have focused mainly on the activation of microglia 3 . However, several recent studies have shown that a dysfunctional blood–brain barrier associated with vascular inflammation and leukocyte migration into the brain contribute to the pathogenesis of AD 3–5 . In particular, we and others have shown that circulating leukocytes adhere to the endothelium in cerebral vessels and migrate into the brain parenchyma in AD patients and in transgenic animals with AD-like disease 37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation